(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The way of presentation of the subject of absolute value and absolute value inequalities in the curriculum and textbooks and the way of teaching the subject creates learning difficulties related to the subject. The purpose of this research is to examine how the teaching of the subject within a technology-based environment differs from the traditional approach in terms of learning difficulties of students. This study has been conducted as an action research. The participants of the research consisted with 34 students who are in the first year of high school. The subject of absolute value and inequalities was taught in a technology-based classroom within the timeframe specified in the curriculum through a researcher as teacher approach. The lecture notes of the students, the classroom observations and the test were used as data collection tools. The data obtained were analyzed descriptively in line with the research problems. The findings showed that interactive teaching using the smart board whit different activities was downloaded appeared to have a positive effect on reducing the known learning difficulties of students about absolute value and increased students’ academic success. In addition, unlike the traditional classroom environment, smart board activities have been observed to increase students’ motivation and interest in lessons. Under the light of the results obtained in the research, suggestions for the use of smart boards were made in the teaching of absolute value inequalities.